The Relationship between Sleep Problems and Health Related Quality of Life among Pediatric Liver Transplant Recipients - Fredericks, Emily M. (2012)
RATIONALE: Among adult liver transplant recipients, sleep disturbances and fatigue are common. Sleep problems following pediatric liver transplantation may contribute to daytime fatigue and lower HRQoL. The aim of this cross-sectional study was to determine the impact of sleep problems on child HRQoL in pediatric liver transplant recipients using validated measures of sleep and quality of life. METHODS: Participants included 47 liver transplant recipients (LTR). The mean age of patients was 10.9 years ± 4.6, and the mean time since transplant was 6.2± 3.9 years. The primary indication for transplantation was biliary atresia (51%). RESULTS: Based on parent report, pediatric transplant recipients had symptoms of sleep disordered breathing, excessive daytime sleepiness, daytime behavior problems, and restless legs. 40.4% of parents and 43.8% of children reported significantly lower child Total HRQoL. Age, time since transplantation and health status variables were not significantly related to quality of life. Hierarchical regression analyses revealed that the sleep-disordered breathing subscale of the Pediatric Sleep Questionnaire accounted for significant variance in parent-proxy reports on the PedsQL summary scales measuring child Psychosocial Health (R(2)=0.38, p < 0.001), Physical Health (R(2)=0.19, p=0.004), and Total HRQoL (R(2) =0.35, p < 0.0001). Across the subscales of the PedsQL, sleep-disordered breathing accounted for significant variance on the child self-reported school functioning scale (R(2) = 0.18, p=0.033). Clinically significant sleep problems were more common among children with low Total HRQoL. There were no significant group differences based on child self-report. CONCLUSIONS: Sleep problems were common in this cohort of pediatric liver transplant recipients and predicted significant variance in parent-proxy reports of HRQoL. Prospective larger scale studies are needed to assess factors that may lead to sleep difficulties and low HRQoL in this population. Appropriate detection of significant sleep problems may lead to interventions that could benefit the quality of life of pediatric LTR.